A Comprehensive Review of the Versatile Dehydration Processes - Jovanovic, Jelena D. (IntechOpen, 2023)
This book provides a comprehensive overview of dehydration techniques. It includes six chapters that discuss various methods of food dehydration. Some of these processes include advanced drying methods that utilize microwaves, infrared radiation, and radio frequency, as well as techniques like hot air, vacuum, fluidized bed, and freeze-drying. Chapters explore the advantages and disadvantages of the various processes, including hybrid techniques that increase the efficiency of drying and improve the quality of the dried products. Other topics explored include the kinetics of hydrogel dehydration and pre-treatment processes such as those that utilize ultrasound.